Net clinical benefit of rivaroxaban compared with warfarin in atrial fibrillation: results from ROCKET AF - Barnett, Adam; Hacke, Werner (International journal of cardiology, 2018)
Aims: The aim of this study was to determine the net clinical benefit (NCB) of rivaroxaban compared with warfarin in patients with atrial fibrillation. Methods: This was a retrospective analysis of 14,236 patients included in ROCKET AF who received at least one dose of study drug. We analyzed NCB using four different methods: (1) composite of death, stroke, systemic embolism, myocardial infarction, and major bleeding; (2) method 1 with fatal or critical organ bleeding substituted for major bleeding; (3) difference between the rate of ischemic stroke or systemic embolism minus 1.5 times the difference between the rate of intracranial hemorrhage; and (4) weighted sum of differences between rates of death, ischemic stroke or systemic embolism, intracranial hemorrhage, and major bleeding. Results: Rivaroxaban was associated with a lower risk of the composite outcome of death, myocardial infarction, stroke, or systemic embolism (rate difference per 10,000 patient-years [RD]=−86.8 [95% CI −143.6 to −30.0]) and fatal or critical organ bleeding (−41.3 [−68 to −14.7]). However, rivaroxaban was associated with a higher risk of major bleeding other than fatal or critical organ bleeding (55.9 [14.7 to 97.2]). Method 1 showed no difference between treatments (−35.5 [−108.4 to 37.3]). Methods 2-4 favored treatment with rivaroxaban (2: −96.8 [−157.0 to −36.8]; 3: −65.2 [−112.3 to −17.8]; 4: −54.8 [−96.0 to −10.2]). Conclusions: Rivaroxaban was associated with favorable NCB compared with warfarin. The NCB was attributable to lower rates of ischemic events and fatal or critical organ bleeding.